Rage against the Iron Cage - Dobbin, Frank; Schrage, Daniel; Kalev, Alexandra (American Sociological Review, 2015)
Organization scholars since Max Weber have argued that formal personnel systems can prevent discrimination. We draw on sociological and psychological literatures to develop a theory of the varied effects of bureaucratic reforms on managerial motivation. Drawing on self-perception and cognitive-dissonance theories, we contend that initiatives that engage managers in promoting diversity—special recruitment and training programs—will increase diversity. Drawing on job-autonomy and self-determination theories, we contend that initiatives that limit managerial discretion in hiring and promotion—job tests, performance evaluations, and grievance procedures—will elicit resistance and produce adverse effects. Drawing on transparency and accountability theories, we contend that bureaucratic reforms that increase transparency for job-seekers and hiring managers—job postings and job ladders—will have positive effects. Finally, drawing on accountability theory, we contend that monitoring by diversity managers and federal regulators will improve the effects of bureaucratic reforms. We examine the effects of personnel innovations on managerial diversity in 816 U.S. workplaces over 30 years. Our findings help explain the nation’s slow progress in reducing job segregation and inequality. Some popular bureaucratic reforms thought to quell discrimination instead activate it. Some of the most effective reforms remain rare.